The Validity Of Learning Media E-learning Based On Edmodo On Kingdom Protist Material Class X SMA/MA - Rachmad Hidayat; Lufri Lufri; Dezi Handayani; Rahmawati Darussyamsu (Universitas Negeri Padang, 2019)
The development of Science and Technology has had a very significant impact on all aspects of human life, including in the field of education. One example of the use of technology in the learning process that is often used is the use of e-learning. E-learning is a system operation that utilizes information technology in learning. One of the e-learning media is edmodo. Edmodo is a social networking based learning platform intended for teachers, students and parents of student. This type of research is research and development (R & D) research with using the 4D Model. The object of this research is the edmodo based e-learning. The learning media is Kingdom Protist material for the X grade students of the SMA Adabiah Padang. The subject of this research were two lecturers Jurusan Biology FMIPA UNP and one teacher of SMA Adabiah Padang as the validator of using this e-learning. The result of validation show an average value of 90.98 with a very valid category. This shows of edmodo based e-learning developed is very valid among in terms of the feasibility aspects of content, language, presentation, and graphic aspects.